Surface Reflectance Overview - Dong, Yue; Lin, Steve; Guo, Baining (Material Appearance Modeling: A Data-Coherent Approach, 2013)
The second chapter provides a brief review of existing work on the acquisition and modeling of opaque surfaces. First, various approaches are discussed on acquisition of a material’s surface reflectance, including methods based on direct measurement and techniques that take advantage of angular or spatial coherence in the data. This is followed by a description of interactive techniques for material modeling and editing.